Evolution of Cross-Neutralizing Antibody Specificities to the CD4-BS and the Carbohydrate Cloak of the HIV Env in an HIV-1-Infected Subject - Mikell, Iliyana; Stamatatos, Leonidas (PLOS ONE, 2012)
Broadly neutralizing antibodies are considered an important part of a successful HIV vaccine. A better understanding of the factors underlying their development during infection and of the epitopes they target is needed to elicit similar antibody responses by vaccination. We and others reported that, on average, it takes 2 to 3 years for cross-reactive neutralizing antibodies to become detectable in the sera of HIV-1-infected subjects and that they target a limited number of epitopes on the HIV Envelope. Here we investigated the emergence and evolution of the earliest cross-reactive neutralizing antibody specificities in one HIV-1-infected individual, AC053. We defined two distinct epitopes on Env that are targeted by the broadly neutralizing antibody responses developed by AC053. The first specificity became evident at 3 years post infection and targeted the CD4-binding site of Env. Antibodies responsible for that specificity neutralized most, but not all, viruses susceptible to neutralization by the plasma antibodies of AC053. The second specificity became apparent approximately a year later. It was due to PG9-like antibodies, which were able to neutralize those viruses not susceptible to the anti-CD4-BS antibodies in AC053. These findings improve our understanding of the co-development of broadly neutralizing antibodies that target more than one epitope during natural HIV-1-infection in selected HIV+ subjects. They support the hypothesis that developing broadly neutralizing antibody responses targeting distinct epitopes by immunization could be feasible.